Description and visualization of the highly dynamic behavior of the electrorheological effect. (January 2020) - Bauerochs, Tobias; Huo, Xiaoye; Yossifon, Gilad; Ulrich, Stephan; Schneider, Steffen; Bruns, Rainer
When an electrorheological fluid is located between two electrodes and an electrical voltage is applied to them, the particles in the fluid move and form chains along the electric field lines. This phenomenon is called the electrorheological effect. The exact behavior of the particles has not yet been studied completely. Some optical investigations of particle motion or behavior have been performed, but did not take into account the high dynamic range directly after the application of an electric field. This study is intended to help explain how the particles behave when they encounter an electric field and then try to align themselves with it. There is an investigation into how these chains develop in a microchannel within milliseconds. For this purpose, the particle behavior of the electrorheological fluid is investigated with high dynamic imaging using a microscope. A high-speed camera records videos of the first milliseconds at 3000 fps synchronously with the application of an electric field. The results provide a better understanding of the chain formation and particle behavior of the electrorheological effect in the high dynamic range and can be used for the design of electrorheological applications as well as simulations of the particle movement.